2014
DOI: 10.1016/j.ijpharm.2014.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission monitoring from a lab scale high shear granulator—A novel approach

Abstract: A new approach to the monitoring of granulation processes using passive acoustics together with precise control over the granulation process has highlighted the importance of particle-particle and particle-bowl collisions in acoustic emission. The results have shown that repeatable acoustic results could be obtained but only when a spray nozzle water addition system was used. Acoustic emissions were recorded from a transducer attached to the bowl and an airborne transducer. It was found that the airborne trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Watson et al [104] developed a monitoring system that can identify different stages of the granulation process by combining a high-speed camera with AE to study the influence of process variables on granulation. This work showed that AE monitoring was beneficial to the monitoring of the wet granulation process.…”
Section: Pat Implementation In Pharmaceutical Granulation Techniquesmentioning
confidence: 99%
“…Watson et al [104] developed a monitoring system that can identify different stages of the granulation process by combining a high-speed camera with AE to study the influence of process variables on granulation. This work showed that AE monitoring was beneficial to the monitoring of the wet granulation process.…”
Section: Pat Implementation In Pharmaceutical Granulation Techniquesmentioning
confidence: 99%
“…Acoustic signals are calibrated with different mixing states which are then correlated with the signals emanating from the mixing vessel to predict mixing states and end points [185]. The frequency of beats pattern and the vibrational modes of the acoustic signals have been found to depend on the material properties [186] and size [187] of the particles being mixed [188].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies performed by Watson et al [185] noted that the acoustic technique can be used to identify formation of excessively large granules due to over-wetting and thus could also be used to identify faults in the process. A few studies such as that of Crouter et al [198] and Crouter [183] Another challenge to the large-scale adoption is that acoustic methods can only be applied to systems where appreciable acoustic emissions are produced such that their evolution can be tracked and converted to data that describes the process under scrutiny [188].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…endpoint of granulation like Near Infrared Spectroscopy 4 , acoustic emission monitoring 5 , power consumption 6 , etc. Previously, powder rheological measurements along with thermal effusivity have been established as a tool to determine the optimum region for wet granulation endpoint, using water and Microcrystalline Cellulose PH 101 (MCC) 7 .…”
mentioning
confidence: 99%